Contributions of the timing and context of racial discrimination to health in Aboiriginal and Torres Strait Islander peoples - Cave, Leah (My University, 2021)
Racism is a social determinant linked to negative health outcomes in children and adults internationally. This thesis applied various quantitative analytic techniques to Australian longitudinal and cross-sectional studies - presenting studies which are among the few to explicitly focus on racial discrimination in children under 13 years, and the first to examine age of first exposure, incorporate racism into latent class analysis, and link racism to allostatic load in adults. Strong evidence for adverse mental health was observed in Aboriginal children under 15 years, while evidence of physiological dysregulation was observed in Aboriginal adults with high psychosocial stress and adverse health.
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Health and wellbeing